Mothers’ employment and its consequences for investment in children - Michoń, Piotr (Investing in Children. Innovative Solutions to Improve Children’s Well-Being, 2018)
The paper was drafted under implementation of a research project “Welfare State and inequalities in subjective well-being – comparative studies of European countries”, financed with funds of the National Science Centre (No. 2013/11/B/HS5/03618).